2016
DOI: 10.1182/blood.v128.22.5178.5178
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Duration of Neutropenia and Lymphopenia on AML Patients Undergoing Induction Chemotherapy

Abstract: Background: Various demographic, clinical and cytogenetic factors have been shown to affect the outcome of patients with acute myeloid leukemia (AML). Some of these risk factors are well-described with performance status and patient age being principal predictors of early death while cytogenetic and molecular factors allow stratification into prognostic categories. However, several critical factors have not been adequately assessed. Typically AML patients treated with standard induction chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…In 10 This is in contrast to a study by Malkan et al where the incidence of neutropenia was found to be 55%. This may be due to the higher percentage of B cell ALL in the group where the incidence of neutropenic fever was lower.…”
Section: Discussioncontrasting
confidence: 65%
“…In 10 This is in contrast to a study by Malkan et al where the incidence of neutropenia was found to be 55%. This may be due to the higher percentage of B cell ALL in the group where the incidence of neutropenic fever was lower.…”
Section: Discussioncontrasting
confidence: 65%
“…This continues until the onset of neutrophil recovery, supporting the role of neutrophil and neutrophil precursors in clearing pegfilgrastim [24]. Also, patients with acute myeloid leukaemia are often neutropenic as a result of their disease [34] and often experience neutropenia following chemotherapy [35]. This results in greater pegfilgrastim exposure compared with patients with other types of cancer undergoing chemotherapy [27,33,36].…”
Section: Discussionmentioning
confidence: 96%